Strategi Pengembangan Daya Saing UMKM Soto Cak Udin Dalam Menghadapi Persaingan Pasar - Permata, Friska Gania; Apriadi, Deri (Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
Micro, Small, and Medium-Sized Businesses (MSMEs) are vital to Indonesia's economy, especially when it comes to boosting local economic structure and creating jobs. MSMEs must create flexible strategies in order to endure and preserve long-term competitiveness in the face of fiercer market competition. The purpose of this study is to determine and evaluate the competitive development tactics used by Soto Cak Udin, a traditional culinary MSME in Bandung City. By gathering information through document analyses, participatory observation, and in-depth interviews, this study uses a descriptive qualitative methodology. According to the research findings, Soto Cak Udin uses a number of competitive development strategies, such as preserving a consistent product taste, offering prompt, friendly service, promoting using straightforward digital platforms like Google Maps and WhatsApp, keeping the workplace comfortable and clean, and encouraging goodwill between the owner and staff. The owner also maintains a straightforward yet orderly approach to financial administration, which contributes to the long-term viability of the company. These results support the idea that improving MSME competitiveness, particularly in the traditional culinary industry, requires strong internal management, digital adaption, service quality, and product differentiation. It is anticipated that other MSME actors would use this research as a guide when developing pertinent and contextual business strategies in the face of fierce market rivalry.